2018
DOI: 10.17116/jnevro201811809128
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin in treatment of lower limb spasticity in patients with brain damage

Abstract: Цель исследования. Разработка и апробация методики обследования пациентов со спастичностью в ногах, описание паттернов спастичности нижних конечностей для пациентов с очаговым повреждением головного мозга и оценка эффективности применения ботулинического нейротоксина типа А (БоНТ) в реабилитации пациентов с последствиями острого нарушения мозгового кровообращения. Материал и методы. Обследовали 56 пациентов со спастическим парезом нижней конечности в возрасте 31-68 лет, которым была назначена терапия БоНТ (дис… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
(20 reference statements)
0
2
0
3
Order By: Relevance
“…As a practical information, bioactive metabolites form and maintain significant steady-state concentrations in blood and liver when supra-nutritional dosages of vitamin E are administered for a sufficient time (> 1 week) to humans and animals [206,207,210], compatible with treatment conditions of previous clinical trials that demonstrated positive effects on patients affected by drug-resistant epilepsy treated for one month with a dosage of 600 IU/day [16] or for 6 months with 400 IU/day [18]. Hopefully, these new aspects of vitamin E metabolism and function may also help to explain conflicting results obtained in other clinical trials (discussed in Section 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a practical information, bioactive metabolites form and maintain significant steady-state concentrations in blood and liver when supra-nutritional dosages of vitamin E are administered for a sufficient time (> 1 week) to humans and animals [206,207,210], compatible with treatment conditions of previous clinical trials that demonstrated positive effects on patients affected by drug-resistant epilepsy treated for one month with a dosage of 600 IU/day [16] or for 6 months with 400 IU/day [18]. Hopefully, these new aspects of vitamin E metabolism and function may also help to explain conflicting results obtained in other clinical trials (discussed in Section 1).…”
Section: Discussionmentioning
confidence: 99%
“…Since the brain is highly susceptible to oxidative stress due to its low antioxidant enzyme activity, and considering that a wealth of studies have indicated that free radicals can act as a pathogen in the epilepsy disease [12,13], natural compounds with antioxidant properties have been evaluated over time in order to find out a therapeutic strategy for preventing the development of epilepsy in patients at risk, by lowering seizure-triggered maladaptive neural plasticity underlying epileptogenic processes [14,15]. In this context, clinical evidence from one study published in 1984 by Kovalenko and colleagues [16] revealed the capability of α-tocopherol (α-T), the vitamin E isoform with the highest in vivo biological activity and bioavailability [17], to improve seizure control in drug-resistant patients. The study recruited seventeen patients suffering from various forms of epilepsy and exhibiting a resistance to the anticonvulsant and psychotropic therapies; they received α-T treatment throughout a month after which the following beneficial effects were observed: 1. improvement of electroencephalogram (EEG) outcome in terms of reduction of pathological signs; 2. significant decrease of seizure frequency, up to be completely arrested in four patients; 3. abatement of lipid peroxidation product plasma levels.…”
Section: Introductionmentioning
confidence: 99%
“…При анализе спастичных мышц нижней конечности были использованы предложенные нами в 2017 г. два основных встречающихся у пациентов с последствиями инсульта паттерна -динамический (ДП) и статический (СП) [21].…”
Section: по используемым приемам тестированияunclassified
“…Обсуждение. За последние 10 лет единственным примером выделения специфических паттернов спастичности являются выделенные нами СП и ДП для мышц нижней ко-нечности пациентов с инсультом [21]. При этом в паттернах спастичности в руке по H. Hefter [5] наш анализ показал совпадение до 80% мышц, т. е. выделенные H. Hefter паттерны не приводят к должной дифференциальной диагностике и не позволяют принять решение о выборе мышц-мишеней.…”
Section: Models Of Post-stroke Patients With Arm Spasticityunclassified
“…Пациентам выполнялись: неврологический осмотр, выявление спастичности мануальным мышечным тестированием, оценка по модифицированным шкалам Эшворта (MAS), Тардье (MTS), комитета медицинских исследований (MRCS), Рэнкина, индексу мобильности Ривермид (RMI), тесту баланса Берга (ТББ), и комфортной ходьбы (КХ) на 10 м и визуально аналоговой шкалы (ВАШ) для определения степени удовлетворенности лечением [10][11][12][13]. К критериям исключения относились: наличие суставных контрактур; краткая шкала оценки психического статуса (MMSE) <24 баллов, парез в ноге MRCS <2; парез в руке MAS <3, спастичность в руке MAS >2.…”
Section: материалы и методыunclassified